Kaidah dalam Interaksi dan Interpretasi terhadap Nas-nas Tanda Hari Kiamat - Lukmanul Hakim Sudahnan; Muhammad Yusram (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2019)
This study aimed to examine the types of interpretations of passages about the signs of doomsday, the wisdom of passages on tribulations and signs of doomsday, the law referring concordance between signs of doomsday and specific occurrences or individuals, and rules in interpreting passages about the signs of doomsday. This research employed qualitative-descriptive approach with content analysis technique and library research. The results of the study show that: (1) there are two types of interpretations of the passages on the signs of doomsday, those are: first, describing those passages and describing the characteristics and details of events according to what is mentioned in the passages; second, identifying the concordance between signs of doomsday and specific occurrences or individuals; (2) among the wisdoms of the passages related to end of time : as proof of the truth of the Prophet's message, as a test for the faith of men, and so that he prepares himself heading toward the end of the day; (3) the law referring the concordance between signs of doomsday and specific occurrences or individuals is allowed, by ensuring the validity (authenticity) of the narrations and not determining the truth of the concordance; (4) rules or principles that must be considered in interpreting passages relating to doomsday are to ascertain Quran and Sunnah as the primary source, verifying the validity of the hadith, not inventing (takalluf), being thorough, not precisely determining the year or the time of doomsday.